(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study looks at Kolkata's potential for sustainable gastronomy tourism, emphasizing how to draw visitors by utilizing the city's rich culinary legacy while evaluating the advantages and disadvantages of the infrastructure that is now in place. It highlights the important economic effects of culinary tourism and how it boosts the local economy by creating jobs and supporting small businesses. The study's SWOT analysis identifies prospects for the strategic application of technology and digital marketing, as well as for the creation of new culinary tourist goods. There are suggestions for best practices, community involvement, and sustainable sourcing along with an analysis of challenges pertaining to the environment, economy, society, and policies. Kolkata can improve its culinary tourism industry and ensure long-term viability and cultural preservation by encouraging collaboration among stakeholders.